2011
DOI: 10.5543/tkda.2011.01490
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of regional left ventricular functions by strain and strain rate echocardiography in type II diabetes mellitus patients without microvascular complications

Abstract: The frequency of left ventricular diastolic dysfunction was higher in patients with DM. Irregular distribution of systolic S and Sr indices in the left ventricular segments may indicate that DM leads to heterogeneous myocardial involvement also in the early period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It indicated that in the presence of diabetes, hypertension could produce more obvious LV hypertrophy and remodeling. Diabetes is a well-established risk factor for developing cardiovascular disease [ 21 ] and diabetic hypertensive patients may have more severe clinical and morphologic features of cardiovascular disease compared to those with hypertension only [ 22 , 23 ]. Recent studies in mice models further found that diabetes by itself had no overt effect on cardiac structural change, but that combined with hypertension, diabetic heart appeared to potentiate LV hypertrophic remodeling [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It indicated that in the presence of diabetes, hypertension could produce more obvious LV hypertrophy and remodeling. Diabetes is a well-established risk factor for developing cardiovascular disease [ 21 ] and diabetic hypertensive patients may have more severe clinical and morphologic features of cardiovascular disease compared to those with hypertension only [ 22 , 23 ]. Recent studies in mice models further found that diabetes by itself had no overt effect on cardiac structural change, but that combined with hypertension, diabetic heart appeared to potentiate LV hypertrophic remodeling [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strain and SR derived from SRI reflect an improved assessment of myocardial contraction and quantification of regional myocardial deformation in humans. [ 31 ] Particularly in the clinical setting, cardiovascular risk factors contributing to altered SRI measures occur before the development of global LV dysfunction. [ 32 ] In addition, the technology's allure lies primarily in its portability, relative affordability, widespread availability, noninvasive nature, and rapid real-time imaging capabilities.…”
Section: Onclusionsmentioning
confidence: 99%
“…Patients with type 2 DM are at high risk of developing CV disease (21). In addition, the clinical and morphologic features of CV disease are more severe in hypertensive diabetic patients compared to lone hypertensive or diabetic patients (22).…”
Section: Discussionmentioning
confidence: 99%